ATOPIC DERMATITIS AMONG CHILDREN: ZONE OF CLINICAL SUPERVISION - L.M. Ogorodova; E.V. Deeva; I.A. Deev ("Paediatrician" Publishers LLC, 2007)
The urgency of atopic dermatitis among children is defined not only the considerable spread of a disease and low quality of life along with this pathology, but above all by such disease peculiarities, as the firm growth of severe incapacitating forms, torpidity towards conventional therapy, continuously recurrent run. In spite of the above said, the regulatory documents still have no such a term, as «disease control», which is why, the objective of the atopic dermatitis therapy has not been defined yet. The absence of «disease control» criteria is accompanied by the incorrect relation between the «severity degree» and «exacerbation» of a disease. In this respect, the main tactics of a doctor, when treating atopic dermatitis, is currently just the therapy of exacerbations. Nevertheless, there are now pharmacotherapeutic modes, allowing one to considerably expand the zone of clinical atopic dermatitis supervision among children during prolonged preventive use. Key words: children, atopic dermatitis, treatment.